The Effect Of Addition Gelatin To The Quality Of White Sweet Potato Jam - Putri, Yolanda; Holinesti, Rahmi; Gusnita, Wiwik; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This study aims to analyze the effect of addition gelatin as much as 0.5%, 1% and 1.5% on the quality of color, aroma,soft texture, texture easily smeared and taste of white sweet potato jam. This type of research is a pure experiment with a completely randomized design method. The data used are primary data obtained directly from 3 expert panelists byfilling out the organoleptic test format on the quality of white sweet potato jam with the addition of gelatin. The dataobtained is then tabulated in tabular form and an Analysis of Variance (ANAVA) is performed, ifFcount > Ftable thenproceed with Duncan's test. The results showed that there was a significant effect of the addition of 0.5%, 1%, and 1.5% gelatin on the quality of the soft texture and easily smeared texture, while the quality of color, aroma, and taste had noeffect. The results of data analysis obtained the highest achievement score overall, namely color 4.44 (1.5%), aroma 3.89(1.5%), soft texture 4.44 (1.5%), texture easily smeared 4.44 (1.5%), and taste 4.22 (1.5%). The best quality test results for white sweet potato jam with the addition of gelatin were in the X₃ treatment with the addition of 1.5% gelatin